The presence of Homoeoneuria s.s. (Ephemeroptera: Oligoneuriidae) in South America with the description of a new species - Salles, F. F.; Francischetti, C. N.; Soares, E. D. G. (Zootaxa, 2009)
In the present work a new species of Homoeoneuria is described based on nymphs and adults from Southeastern Brazil. Based on cladistics, the new species belongs to the subgenus Homoeoneuria.s.s. Homoeoneuria (H). watu sp. n., besides being the second species of the genus reported from South America, is the first representative of the subgenus from the region. The new species can be distinguished from the other described species of the genus by the following combination of characters: In the adult stage, (1) pronotum with prominent posteromedian pale yellow spot almost reaching anterior margin; (2) abdominal color pattern; (3) shape of penes. In the nymph, (1) head heavily washed with brownish-orange between compound eyes and ocelli; (2) antennal pedicels with short, thick setae; (3) small paired tubercles present on vertex and anterior margin of pronotum; (4) galea-lacinia of maxillae with submarginal row of 20–21 long, spinous setae; (5) abdominal color pattern. Comments on the biology of the new species are also provided.